PHYSICAL-MECHANICAL PROPERTIES OF PINEAPPLE LEAF FIBRE REINFORCED IN UNSATURATED POLYESTER RESIN FILLED WITH CALCIUM CARBONATE - Rachman, Maulana; Kasda, Kasda; Komara, Achmad Moeslihat; Gunawan , Harjadi; Setyanto, Djoko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Using natural fibres is often recommended as polymer composite materials owing to their potential to reduce the pollution of synthetic material waste. This study aimed to obtain the physical properties of unsaturated polyester resin matrix composite containing calcium carbonate fillers of 15 and 30 parts per hundred weights of the resin and natural pineapple leaf fibre of the amount 20% and 30% of the composite weight. The composite samples were three millimetres thick, with the pineapple leaf fibres arranged in one longitudinal direction. Some parameters observed included density, water absorption, response to fire, hardness, tensile strength, modulus of elasticity, and impact strength. The results showed that adding calcium carbonate filler into the matrix increased the density, water absorption, hardness, and modulus of elasticity of the composite. However, it reduced the flame propagation rate, tensile strength, and impact strength. Also, the use of pineapple leaf fibre contributed to increased water absorption, rate of flame propagation, tensile strength, modulus of elasticity, and impact strength of the composite, but it reduced the density and hardness. As these samples use economical materials, they are likely valuable for building materials that do not require high mechanical properties, especially guttering materials.